2015
DOI: 10.1259/bjr.20150197
|View full text |Cite
|
Sign up to set email alerts
|

Salvage image-guided intensity modulated or stereotactic body reirradiation of local recurrence of prostate cancer

Abstract: Our series, based on experience in one hospital alone, shows that re-EBRT for local relapse of prostate cancer is feasible and offers a 2-year cure in about half of the patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
70
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(80 citation statements)
references
References 16 publications
6
70
1
Order By: Relevance
“…7,12 As far as reirradiation is concerned, the vast majority of patient series were treated with brachytherapy (BRT). In the last years, along with the improvement in radiotherapy (RT) planning and delivery technology, several reports on salvage EBRT have been published [14][15][16][17][18][19][20][21][22][23][24][25][26][27] (Table 1).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…7,12 As far as reirradiation is concerned, the vast majority of patient series were treated with brachytherapy (BRT). In the last years, along with the improvement in radiotherapy (RT) planning and delivery technology, several reports on salvage EBRT have been published [14][15][16][17][18][19][20][21][22][23][24][25][26][27] (Table 1).…”
mentioning
confidence: 99%
“…19,[28][29][30] Our reports include numerous primary tumor sites, and the majority of studies are focused on the recurrent PCa. 14,15,19,[28][29][30][31][32][33][34] In particular, the preliminary retrospective analysis published by Zerini et al 14 with a mean follow-up of 21.3 months, reported good local tumor control and low toxicity profile in a series of 32 patients treated with IG-IMRT for isolated local recurrence of PCa. The aim of the current study was to present the outcome in the larger patient series treated with salvage SBRT (re-EBRT), including updated information of some patients from Zerini's series.…”
mentioning
confidence: 99%
“…There does appear to be a dose-response for GU toxicity, as an earlier study using 30 Gy in five fractions reported a 7% incidence of late grade 3 GU toxicity, and no late grade 3 toxicities were identified in a small cohort of patients treated with 25-30 Gy in five fractions. 30,31 Serious GI toxicity was not reported in any of these studies. Given that the grade $3 toxicities appear to be at least twice as common with salvage SBRT compared with upfront SBRT, the dosimetric improvements seen with HG plans may be more clinically meaningful in the salvage setting.…”
Section: Discussionmentioning
confidence: 88%
“…In the reirradiation setting, however, rates of long-term adverse are likely to be higher, and clinical data are still emerging. Several recent series [30][31][32] exploring the outcomes of salvage SBRT in this setting have reported late CTCAE grade $3 GU toxicity rates after salvage SBRT approach of 7%. The purpose of this study was to assess the magnitude of the dosimetric advantages offered by performing HG prostate SBRT, with the hypothesis that the dosimetric benefits would be large enough to suggest a clinical benefit, particularly in the salvage setting.…”
Section: Introductionmentioning
confidence: 99%
“…Despite numerous studies on reirradiation for various tumors sites, experience in retreatment of prostate cancer is very limited and includes mainly brachytherapy series [1]. Since the review by Alongi et al in 2013 [1], a couple of new series have been published and show that both technology and radiobiology play a role [2,3]. Using advanced imaging (recurrence identified by magnetic resonance, staging based on [ 18 F]-fluorocholine positron emission tomography), highly selective radiotherapy modalities (stereotactic body radiotherapy and image-guided intensity-modulated radiotherapy), and extreme hypofractionation (doses > 6 Gy/fraction), Janoray et al showed that reirradiation is safe and may offer a medium-term cure in a good proportion of patients.…”
Section: Expert's Summarymentioning
confidence: 99%